(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Applications of digital technology in contemporary architecture provide new possibilities for the creation of architectural form, structural design, production of components and construction, as well as providing the potentiality to test architectural performance. As a result new relationships has been appeared between architectural form and its structure, which varies depending on digital models selected at the start of computing process and the different digital input parameters for the programs chosen by the designer.The use of digital programs in architectural design is reflected on buildings facades, where it varies in the appearance or disappearance of tectonic values. In light of this, the problem of research is: The need to identify the methods of generating the shape and its relationship to the structure in digital architecture and its impact on the availability of tectonic value in the digital patterns of the facades The research hypothesis is: the methods of generating the architectural form and its relation to the structure in digital architecture are factors in the availability or unavailability of tectonic value in the digital patterns of the facades. The goal of the research is: to identify the methods of generating the shape and its relation to the structure in the digital architecture and its effect on the availability or of tectonic value in the digital patterns of the facades. The research follows a methodology with the five-step: first, the classification of design processes in digital architecture. Second, identifying of the processes of the digital structural design. Third, studying the impact of the relationship between the architectural design and structural design of the building. Fourth, study the role of tectonic patterns in architectural facades. Fifth, analysis of the impact of the type of digital design processes and the relationship between architectural design and structural design of the building in the case studies. The research concluded that the integrative digitizing process of the design of the and structure may not provide the tectonic value in the facade patterns, because It also depends on the type of design process of the facades as well and if it is being included or not included in the digital design process of the form or structure or both.